Calibration of an airborne γ-ray spectrometer based on an unmanned aerial vehicle using a point source. (1st December 2022) - Qin, Guoxiu; Xu, Youning; Li, Fan; Zhou, Wenping; Li, Weizhe; Zhao, Guozhi
Highlights: An airborne γ-ray spectrum survey system based on unmanned aerial vehicle was designed to meet the needs of detection efficiency and energy resolution for airborne γ-ray spectrometry. A calibration method of airborne γ-ray spectrum survey system based on unmanned aerial vehicle using point source is proposed in this paper. General methods were used to calibrate the airborne γ-ray spectrum survey system, the background of aircraft, influence coefficient of cosmic ray, influence coefficient of radon in the atmosphere, stripping factor, altitude attenuation factor, and sensitivity were obtained. Four artificial radioactive point sources, 241 Am, 57 Co, 137 Cs, and 60 Co, were selected to calibrate the airborne γ-ray spectrum survey system, the altitude attenuation coefficient and response coefficient of different nuclides were obtained. Abstract: Due to the lack of physical calibration models of artificial radionuclides for airborne γ-ray spectrometers, it is difficult to accurately deduce the content of artificial radionuclides on the ground based on airborne γ-ray spectrometry. According to the airborne radiation monitoring standard of the International Atomic Energy Agency (IAEA) and domestic and foreign industry experience, a calibration method for an airborne γ-ray spectrum survey system (AGS) based on an unmanned aerial vehicle (UAV) using point source is proposed in this paper. After calibrating the system with general methods and obtaining satisfactory test results, four artificial radioactive point sources were selected to calibrate the developed AGS and then obtain the calibration parameters for these point sources. Based on the calibration parameters of these four radionuclides, the calibration parameters of other artificial radionuclides can be estimated to realize the function of quantitative measurement of artificial radioactive sources by the AGS based on UAVs.